Um caminho inovador : o projeto educacional da Escola Regional de Merity (1921-1937) - Silva, Vilma Corrêa Amancio da (2008)
To present research investigates, tends as knowledge area the History of the Brazilian Education, an experience new school, the education project of the Escola Regional de Merity, among the years from 1921 to 1937. A founded institution, in 1921, for Armanda Álvaro Alberto, "the pioneer of the New School in Brazil", in the Vila Merity, current municipal district of Duque de Caxias, in the State of Rio de Janeiro. We took as main sources in the elaboration of the researches the annual reports of the school, , program of teaching of "Studies of the Nature", the book documentary on the school organized by Armanda, administrative documents, records doctors, school bulletin, , considered important to the History of the Brazilian Education. The present study has as purposes to present, starting from the documental sources, the mechanisms and pedagogic and social strategies used by the director of the school and her net of relationships, the local community's integration in the several school and extra-school activities there presented. For such, it was necessary to make explicit about Armanda and her relationship with the area of Merity. The school program curricular, had as fundamental beginning the teaching of the hygiene. In that sense, we investigated the actions and educational practices accomplished by the movement hygienist's agents in the Regional School of Merity. Being the Regional of Merity an institution of primary teaching, it fit us the task of we map the process of renewal of the primary education and of the teaching methods, from middles of the century XIX, so that we could notice which went to the innovative proposals inserted in the Brazilian education field. Leaving of that context, we focused our studies in the teaching methods applied in the Regional, based in the theoretical and methodological presuppositions derived of the movement of the New School. We ended that the school, addressing their activities to the local demands, it innovated when applying the teaching regionalizado. The presented research intends to contribute for construction of the History of the Regional Education, that is, of the Baixada Fluminense, and in a special way, to mention on an experience new school, pioneer with respect to the regional teaching. It still to fitted into in the research lines developed by the group of Research memory, History and production of the Knowledge in Education, as part of the project "Intellectuals, to can and leaders' formation in Brazil."